Quote:
Originally Posted by bhagyashree95
I was trying to get the a variables on one side of the equation and the b variables on the other side of the equation but I couldn't. Can anyone else separate these two variables?
( P.S. The equation is in the attached document.)
Thanks for helping!!!

If you are trying to solve for phi then:
(a + b)/(a) = a/b = phi where a > b, and b not equal to 0
Since a/b = phi, cross multiply to get a = b*phi
Substitute b*phi for a giving;
(b*phi + b)/(b*phi) = (b*phi)/b
Cross multiply to get;
(b^2)*phi^2 = (b^2)*phi + b^2
(b^2)*phi^2 = (b^2)(phi + 1)
phi^2 = phi + 1
phi^2  phi  1 = 0
Solve for phi. phi = (1 + sqrt(5))/2 (Ignore the (1  sqrt(5))/2 case).